Predictors of risk and success of obesity surgery - Nickel, Felix; Benner, Laura; Wekerle, Anna-Laura; Billeter, Adrian; Kenngott, Hannes Götz; Fischer, Lars; Müller, Beat P. (Obesity facts, 2019)
Background: Obesity surgery has proven successful for weight loss and the resolution of comorbidities. There is, however, little evidence on its success and the risk of complications when considering age of onset of obesity (AOO), years of obesity (YOO), preoperative body mass index (BMI), Edmonton obesity staging system (EOSS) score, and age as possible predictors of weight loss, the resolution of comorbidities, and the risk of complications. Methods: Patients who underwent Roux-en-Y gastric bypass (RYGB) and laparoscopic sleeve gastrectomy (LSG) from a prospective database were analyzed. Multiple regression analyses were used to predict comorbidities and their resolution, percentage excess weight loss (%EWL) and total weight loss (%TWL) 12 months after surgery, and the risk of complications using the predictors AOO, YOO, age, EOSS, and BMI. Results: 180 patients aged 46.8 ± 11.1 years with a preoperative BMI 49.5 ± 7.5 were included. The number of preoperative comorbidities was higher with older age (β = 0.054; p = 0.023) and a greater BMI (β = 0.040; p = 0.036) but was not related to AOO and YOO. Patients with AOO as a child or adolescent were more likely to have an EOSS score of ≥2. Greater preoperative BMI was negatively associated with %EWL (β = –1.236; p < 0.001) and older age was negatively associated with %TWL (β = –0.344; p = 0.020). Postoperative complications were positively associated with EOSS score (odds ratio [OR] 1.147; p = 0.042) and BMI (OR 1.010; p = 0.020), but not with age. AOO and YOO were not related to postoperative outcome. Conclusion: Greater BMI was associated with a lower %EWL and age was associated with a low %TWL. YOO and AOO did not influence outcome. Age, BMI, and EOSS score were the most important predictors for risk and success after obesity surgery. Surgery should be performed early enough for optimal outcomes.
Gesehen am 22.10.2019